The Influences of Factors Supporting to The Health Promotion of Smokers Based on Green and Krueter Concept - Phanwattana, Pitsarn (Journal of Nursing, Siam University, 2019)
Abstract The objectives of this research were to study (1) Demographic characteristics of smoker in 3 Bangkok health center include Suan Luang, Dok Mai and Lăem Tong athlete village branch. (2) The influence of family strength, knowledge of toxic tobacco, social strength and law of tobacco influence to health promotion of smokers. This study was conducted by quantitative approach, questionnaire was used to collect data from 147 smokers by purposive sampling. The data were analyzed using path analysis. The results indicated that (1) Almost of smokers had male, bachelor degrees, single, private employee, income 30,001 – 45,000 per month. Most of smokers in 37 center had 21-40 years old but smokers in 57 and 68 center had 41–60 years old. (2) Environmental factors supporting had the direct, indirect, and total influences the health promotion of smokers than the education factors supporting.